Aged garlic extract preserves cutaneous microcirculation in patients with increased risk for cardiovascular diseases: A double‐blinded placebo‐controlled study - Wlosinska, Martine (Int Wound J, 2019)
Laser Doppler velocimetry estimates tissue perfusion providing a record of microvascular blood flow. Patients with heart disease or diabetes mellitus have impaired microvascular perfusion leading to impaired wound healing. Aged garlic extract (AGE) has a positive effect on vascular elasticity. This study aimed to assess the effect of long‐term treatment with AGE on cutaneous tissue perfusion. A total of 122 patients with Framingham Risk Score ≥ 10 were randomised in a double‐blinded manner to placebo or 2400 mg AGE daily for 1 year and monitored. Cutaneous microcirculation was measured at 0 and 12 months using laser Doppler velocimetry. A repeated measures analysis of variance (ANOVA) with a Greenhouse–Geisser correction determined that mean post‐occlusive reactive hyperaemia differed significantly between time points. The mean percent change between the two time points 0 and 12 months was 102, 64 (174, 15)% change for AGE and 78, 62 (107, 92)% change for the placebo group (F[1, 120] = 5. 95, P < 0.016), 12 months of AGE increases the microcirculation in patients with an increased risk for cardiovascular events estimated using the Framingham risk score. Increased microcirculation could hypothetically facilitate wound healing.